Hazardous substances in the sediments and their pathways from potential sources in the eastern Gulf of Finland. (September 2021) - Kuprijanov, Ivan; Väli, Germo; Sharov, Andrey; Berezina, Nadezhda; Liblik, Taavi; Lips, Urmas; Kolesova, Natalja; Maanio, Jaakko; Junttila, Ville; Lips, Inga
Abstract: Contamination by hazardous substances is one of the main environmental problems in the eastern Gulf of Finland, Baltic Sea. A trilateral effort to sample and analyse heavy metals (HMs), polycyclic aromatic hydrocarbons (PAHs), and organotins from bottom sediments in 2019–2020 were conducted along with harvesting historical data in Russian, Estonian and Finnish waters. We suggest that the input of organotins still occurs along the ship traffic routes. The tributyltin content exceeded the established quality criteria up to more than 300 times. High contamination by PAHs found near the ports, most likely originate from incomplete fuel incineration processes. The Neva River Estuary and Luga Bay might potentially suffer from severe cadmium contamination. The high ecological risk attributed to the HMs was detected at deep offshore areas. The simulated accumulation pattern qualitatively agrees with field observations of HMs in sediments, demonstrating the potential of numerical tools to tackle the hazardous substances problems. Highlights: Hazardous substances (HS) assessed in the bottom sediments of the Gulf of Finland Organotins (mainly TBT) are the most distributed HS along the shipping routes. Contamination by PAHs increased near the ports indicating fuel incineration. High ecological risk attributed to the heavy metals in the deep offshore areas Simulated HS accumulation pattern in qualitative agreement with field observations